2006
DOI: 10.2106/jbjs.e.01409
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cognitive Function on Outcome After a Hip Fracture

Abstract: The systematic use of the Short Portable Mental Status Questionnaire upon admission to the orthopaedic ward identifies patients with a hip fracture who have severe cognitive dysfunction and effectively predicts their outcome with regard to the ability to walk, ability to perform the activities of daily living, and mortality, and it can be recommended for use in the care of elderly patients with a hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 117 publications
(200 reference statements)
10
39
1
2
Order By: Relevance
“…This is suggestive of recall bias; however, subsequent values for these studies are also higher than those from Czoski-Murray et al [10] implying possible differences in study population. Retro- spective prefracture values and postfracture values for Soderqvist et al [19] are closer to those found in CzoskiMurray et al [10] None of the three studies with prefracture utility values suggest a return to full prefracture health at final follow-up. Most values suggest a nonlinear recovery process.…”
Section: Utility Values For Hip Fracturessupporting
confidence: 78%
See 3 more Smart Citations
“…This is suggestive of recall bias; however, subsequent values for these studies are also higher than those from Czoski-Murray et al [10] implying possible differences in study population. Retro- spective prefracture values and postfracture values for Soderqvist et al [19] are closer to those found in CzoskiMurray et al [10] None of the three studies with prefracture utility values suggest a return to full prefracture health at final follow-up. Most values suggest a nonlinear recovery process.…”
Section: Utility Values For Hip Fracturessupporting
confidence: 78%
“…The results from Borgstrom et al [44], Tidermark et al [17], and Blomfeldt et al [14] are from Sweden and give higher values both pre-and post-hip fracture than those from Soderqvist et al [19] (also from Sweden) or CzoskiMurray et al [10] for the UK. Values for 12 and 24 months in Czoski-Murray et al [10] are considerably higher if only those with full data are considered, but lower when multiple imputation of missing values is used.…”
Section: Utility Values For Hip Fracturesmentioning
confidence: 95%
See 2 more Smart Citations
“…El tratamiento tiene como objetivo recuperar el nivel de independencia y deambulación previo, la reducción quirúrgica se acompaña de una alta incidencia de complicaciones y un prolongado periodo de rehabilitación que incrementa si la resolución es tardía; se calcula que la tasa de mortalidad en un 1 año es cercana al 30 % [6,11,15]; sin embargo, sin cirugía los resultados son pobres e incapacitantes por lo que la cirugía se ha convertido en el tratamiento de elección [11,16,17].…”
Section: Introductionunclassified